Analýza ekonomických ukazatelů pomocí statistických metod - Ivachshenko, Olga (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Bakalářská práce se zabývá finanční analýzou společnosti ABB, s. r. o. za použitím statistických metod. Práce se skládá ze dvou částí. První část se zaměřuje na vysvětlení jednotlivých ekonomických ukazatelů a popisuje regresní analýzu a časové řady. Druhá část obsahuje finanční analýzu společnosti a predikce budoucího vývoje pomocí statistických metod. Na základě analýz jsou popsány doporučení ke zlepšení finanční situace.

The bachelor thesis focuses on the financial analysis of ABB s. r. o company by using statistical methods. The thesis consists of two main parts. The main purpose of the first part is the describing of individually economic indicators of the company and regressive analysis with the time series. The second part includes the financial analysis and the prediction of further development for the company. As the conclusion of these two parts, there is suggested recommendations for improving the financial situation in the future.
Analysis of Economic Indicators Using Statistical Methods
Keywords: finanční analýza; statistické metody; likvidita; regresní analýza; časové řady; ekonomické ukazatele; faktoring; financial analysis; statistical methods; liquidity; regression analysis; time series; economic indicators; factoring